Secondary (Symptomatic) Trigeminal Autonomic Cephalalgia - Chowdhury, Debashish (Ann Indian Acad Neurol, 2018)
Primary trigeminal autonomic cephalalgias (TACs) are uncommon group of headache disorders. These are defined and diagnosed by the criteria given by the International Classification of Headache Disorders 3β version. Over the past few decades, a number of secondary (symptomatic) cases have been described in the literature with headache features indistinguishable from primary TACs. Many structural and other pathologies have been found in these patients that can be causally related to the headaches. This review attempts to critically analyze the existing literature including the new cases published during 2015–2017.